The Role of Global Trends in Stimulating Food Production - Rahimov, Novruz (Acta Universitatis Danubius. Œconomica, 2024)
Meeting the demand for food products has been a pressing issue throughout the development of human society. The emergence of these problems has been closely linked to factors such as population growth and challenges in food production. In essence, as the global population increases exponentially, so does the demand for food products. These challenges, in meeting the demand for food products, often coincide with economic crises and geopolitical tensions, creating more problematic situations. Given all these considerations, there is a greater need for stimulating food production in modern conditions. The process of stimulating food production is particularly relevant in developing countries, where factors contributing to intensity in food production are relatively low and processes related to the application of the latest achievements in agricultural technology are weakly implemented. In modern conditions, the influence of global trends on stimulating food production is more pronounced. This process has its own socio-economic dimensions. Firstly, it is closely related to the deepening of the globalization process in the international relations system, as well as the incorporation of globalization into various aspects of society, including social, economic, and even household life. The globalization process affects not only socio-economic fields but also natural-geographical processes to a significant extent. Global climate change, including global warming and other factors, fundamentally affect food production, creating sharp problems. Particularly, ecological issues, destruction of green spaces, water conflicts, and other factors negatively impact the food production sector. Therefore, considering global trends in stimulating food production is of paramount importance. Considering global trends in stimulating food production primarily entails taking necessary measures to eliminate the adverse effects of these trends.